2019
DOI: 10.3390/rs11050542
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Time Series of Sentinel-1 and Sentinel-2 Imagery to Detect Meadow Phenology in Mountain Regions

Abstract: A synergic integration of Synthetic Aperture Radar (SAR) and optical time series offers an unprecedented opportunity in vegetation phenology monitoring for mountain agriculture management. In this paper, we performed a correlation analysis of radar signal to vegetation and soil conditions by using a time series of Sentinel-1 C-band dual-polarized (VV and VH) SAR images acquired in the South Tyrol region (Italy) from October 2014 to September 2016. Together with Sentinel-1 images, we exploited corresponding Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 72 publications
4
49
1
1
Order By: Relevance
“…Previous studies have shown the potential of C and L-band SAR data to discriminate crop types [16,17], and a significant improvement in classification accuracy has been reported when SAR data and a Landsat8 satellite image time series were integrated [2,18]. Sentinel-1 data have been applied for mapping crop fields with the support of Sentinel-2 data or Landsat-8 data [19][20][21][22]. Besides these, TerraSAR-X and TanDEM-X provide X-band SAR data of high geometric accuracy at a high spatial resolution of 2.5-6 m in 30-km swaths in Stripmap mode [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the potential of C and L-band SAR data to discriminate crop types [16,17], and a significant improvement in classification accuracy has been reported when SAR data and a Landsat8 satellite image time series were integrated [2,18]. Sentinel-1 data have been applied for mapping crop fields with the support of Sentinel-2 data or Landsat-8 data [19][20][21][22]. Besides these, TerraSAR-X and TanDEM-X provide X-band SAR data of high geometric accuracy at a high spatial resolution of 2.5-6 m in 30-km swaths in Stripmap mode [23].…”
Section: Introductionmentioning
confidence: 99%
“…These data, which are distributed free of charge, have an average revisit time of two days between 0 and 45 degrees latitude [18]. As a result, Sentinel-1 data have been widely used for land cover classification [19][20][21], monitoring of phenology [22], and biomass or production estimation. The interferometric wide-swath (IW) mode that offers VV (vertical transmit and receive) and VH (vertical transmit, horizontal receive) polarization data is normally used as the default acquisition mode [23,24].In addition to C-band SARs, the high sensitivity of the sigma naught of X-band sensors has been confirmed, and the potential of the X-band for identifying and forecasting crop growth using indices such as LAI has widely been confirmed [25,26].…”
mentioning
confidence: 99%
“…RapidEye time series to classify PG management practices intensity are processed in [7]. S1 and S2 datasets are proposed for exploring correlation bewteen NDVI and σ 0 over PG in [5], and in [4] for monitoring MowEve and grazing occurrences. Some studies integrate optical multi-sensor data to increase the temporal resolution.…”
Section: B Methodological Analysis: Related Workmentioning
confidence: 99%
“…To address low optical temporal resolution, exponential amount of work is being done to investigate SAR time series for PG monitoring and MowEve assessment as in [9] with COSMO-SkyMed data, and in [10] for PG classification from RapidEye augmented with TerraSAR-X data. The potential of dual-pol capability of S1 to discriminate MowEve and grazing is discussed in [5]. The interest of S1 coherence variation for MowEve detection with 12-days pairs of images over PG in Estonia is also explored in [6].…”
Section: B Methodological Analysis: Related Workmentioning
confidence: 99%